Jiajiejian gel ameliorates thyroid nodules through regulation of thyroid hormones and suppression of the (IL-6, TNF-α, IL-1β)/JAK2/STAT3/VEGF pathway - Wang, Changlin; Gao, Xiangju; Qiao, Mingqi; Gao, Dongmei; Guo, Yinghui; Wang, Jieqiong; Song, Chunhong (Frontiers in Pharmacology, 2024)
Background: Traditional Chinese medicine (TCM) external treatments have unique advantages in treating thyroid nodules, but the currently available external preparations are relatively few and the therapeutic mechanism is unclear. Jiajiejian gel (JJJG) is a TCM external preparation for the thyroid nodule treatment, which has been preliminarily proven to be safe and effective in clinical practice.Objective: The current study was aimed to elucidate the therapeutic effects and the underlying mechanisms of JJJG on thyroid nodules in rats.The contents of paeonol and forsythoside A in JJJG were determined by HPLC. The thyroid nodules rat model was established through oral gavage of 0.1% propylthiouracil (PTU) for 6 weeks and meanwhile the rats were treated with external JJJG (0.26, 0.52, 1.04 g/kg). Subsequently, the therapeutic effect of JJJG was observed by means of ultrasonic examination, morphology observation, organ coefficients determination and histopathological analysis. Mechanismlly, the levels of FT3, FT4 and TSH were measured and transcriptomics were used to analyse and screen the key targets and pathways of alleviating thyroid nodules by JJJG. Further, gene and protein expression levels of key factors were measured and validated using quantitative real-time PCR, ELISA, western blotting and immunofluorescence, so as to clarify the therapeutic mechanism.Results：The contents of the paeonol and forsythoside A were 1.160 and 0.608 mg/g. JJJG reduced thyroid swelling, improved nodular lesions, decreased thyroid coefficients, and inhibited abnormal nodular hyperplasia of follicular epithelial cells. In terms of mechanism, JJJG significantly increased the levels of FT3 and FT4 and decreased TSH in serum. Transcriptomics suggested that the (IL-6, TNF-α, IL-1β)/JAK2/STAT3/VEGF pathway may be one of the key mechanisms in the treatment of thyroid nodules by JJJG. Further validation experiments demonstrated that JJJG significantly reduced the mRNA expression and protein content of IL-1β, IL-6 and TNF-α in thyroid tissue, as well as the mRNA expression of JAK2, STAT3 and VEGF and the protein expression of p-JAK2/JAK2, p-STAT3/STAT3 and VEGF.Conclusions: This study indicates that JJJG efficiently ameliorates thyroid nodules by regulating the levels of FT3, FT4 and TSH in serum and suppressing (IL-6, TNF-α, IL-1β)/JAK2/STAT3/VEGF pathway in thyroid tissue, providing a potential therapeutic approach for thyroid nodules.